Comparative Studies on the Biology and Filarial Susceptibility of Selected Blood-feeding and Autogenous Aedes togoi Sub-colonies - Junkum A. (2014)
Blood-feeding and autogenous sub-colonies were selected from a laboratory, stock colony of Aedes togoi, which was originally collected from Koh Nom Sao, Chanthaburi province, Southeast Thailand. Comparative biology and filarial susceptibility between the two sub-colonies (blood-feeding: F11, F13; autogeny: F38, F40) were investigated to evaluate their viability and vectorial capacity. The results of comparison on biology revealed intraspecific differences, i.e., the average egg deposition/gravid female (F11/F38; F13/F 40), embryonation rate (F13/ F40), hatchability rate (F11/F38; F13/F 40), egg width (F11/F38), wing length of females (F13/F40), and wing length and width of males (F11/F38) in the blood-feeding sub-colony were significantly greater than that in the autogenous sub-colony; and egg length (F11/F38) and width (F13/F40), and mean longevity of adult females (F11/F38) and males (F13/F40) in the blood-feeding sub-colony were significantly less than that in the autogenous sub-colony. The results of comparison on filarial susceptibility demonstrated that both sub-colonies yielded similar susceptibilities to Brugia malayi [blood-feeding/autogeny = 56.7% (F11)/53.3%(F38), 60%(F13)/83.3%(F 40)] and Dirofilaria immitis [blood-feeding/autogeny = 85.7%(F 11)/75%(F38), 45%(F13)/29.4%(F40)], suggesting autogenous Ae. togoi sub-colony was an efficient laboratory vector in study of filariasis.